Optimal iteration and its application to some problems in aerosol science and particle dynamics. Issue 11 (2nd November 2021) - Lewis, Ernie R.
Abstract: Iteration is a common technique for finding the solutions to an equation. It is easy to code, straightforward to apply, readily comprehensible, and can be run indefinitely until a given accuracy is attained. However, for a given equation there are multiple iteration schemes that can be employed, with different convergence rates, and there is no obvious way to determine a priori which is best. Here the convergence rates of different approaches to simple iteration schemes are analyzed and the new technique of optimal iteration, which determines the scheme that maximizes the convergence rate, is introduced and illustrated by its application to several common problems in aerosol and particle dynamics. The first application is determination of the mobility diameter of an aerosol particle from the measured mobility, which is complicated by the nonlinearity of the Cunningham correction. This same equation occurs in the determination of the diameter of multiply charged particles with the same mobility diameter as singly charged particles. The next application is determination of the aerodynamic diameter from the mobility diameter for situations in which the Cunningham correction must be taken into account. The final two applications are determination of the terminal velocity from the diameter, and of the diameter from the terminal velocity, for particles sufficiently large that Stokes' Law does not apply. The technique is easy to apply and can be employed in a number of situations. Copyright © 2021 American Association for Aerosol Research